Research geodemographic processes to identify the dynamics of the population of the region (the example of the Chernivtsi region) - Rudenko, Leonid G.; Leiberiuk, Aleksandr M. (Journal of the Belarusian State University. Geography and Geology, 2019)
The concepts of geodemographic process and geodemography is reviewed together with the object of their research. Based on indicators of natural growth, migration and their resulting value of general growth, the features of geodemographic processes are determined. It is proposed to expand the typology of the existing subtypes of geodemographic processes for the accounting of zero indixes in I and III types of geodemographic processes. By the help of mapping method maps of the Chernivtsi region have been built for the local councils. This maps show types and subtypes of geodemagrafic processes.   The analysis of the dynamics of these indicators are carried out for the period from 2001–2004 and 2014. Districts of theregion are distinguished according to the characteristic features of geodemographic processes and the factors of influence on the peculiarities of formation of geodemographic processes of the region are characterized.
Keywords: geodemography; geodemographic process; Chernivtsi region; local council; positive geodemographic type; stagnation geodemographic type; negative geodemographic type